Respiratory plasticity in the zebrafish (Danio rerio ) - Vulesevic, Branka (University of Ottawa (Canada), 2005)
The aim of this thesis was to investigate respiratory plasticity in zebrafish (Danio rerio) confronted with long-term changes in water gas composition (hypoxia, hyperoxia or hypercapnia) either as embryos or adults. The ventilatory responses to acute changes in water gas composition (hypoxia, hypercapnia or cyanide) were assessed using a non-invasive technique (Altimiras and Larsen, 2000) to continuously monitor breathing frequency (f R) and relative breathing amplitude. The ventilatory response to acute hypoxia consisted of an increase in fR while the response to acute hypercapnia was an increase in relative breathing amplitude. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.